Matrix Remodeling Associated 7 Deficiency Alleviates Carbon Tetrachloride-Induced Acute Liver Injury in Mice - Lin, Dandan; Sun, Zhenjiang; Jin, Ziqi; Lei, Lei; Liu, Yonghao; Hu, Bo; Wang, Benfang; Shen, Ying; Wang, Yiqiang (Frontiers in Immunology, 2018)
Matrix-remodeling associated 7 (MXRA7) was first noted to co-express with a group of matrix remodeling related genes, and its biological functions had remained unclear. In this study, we investigated the presumed function of MXRA7 in a carbon tetrachloride (CCl4)-induced acute live injury model in mice. Wild-type, MXRA7-/- mice, and mice that were pulsed with hydrodynamic injection of vehicle or MXRA7-harboring plasmids were challenged with a single dose of CCl4 for injury induction. The sera, spleens and livers were harvested from mice for assay of cytokines/chemokines expression, cellular responses or histological features. We found that MXRA7 deficiency alleviated, and MXRA7 overexpression aggravated liver damage in CCl4-challenged mice. FACS analysis showed that MXRA7 deficiency reduced the recruitment of neutrophils through down-regulation the expression of CXCL1 and CXCL2 in liver, decreased the number of CD8+ T cells in liver and spleen, suppressed the release of IFNγ and TNFα from T cells, and decreased IFNγ in serum and liver. Western blot assay demonstrated that MXRA7 deficiency suppressed the activation of MAPK pathway and AKT/NF-κB pathway respectively. Lastly, MXRA7 deficiency or overexpression regulated the expression of two matrix remodeling-related genes (fibronectin and TIMP1) in the liver. We concluded that MXRA7 was an active player in CCl4-induced liver injury, hypothetically by mediating the inflammation or immune compartments and matrix remodeling processes. Further exploration of MXRA7 as a possible new therapeutic target for management of inflammation-mediated liver injury was discussed.